Elements of structural dynamics : a new perspective - Roy, Debasish Kumar, 1946-; Visweswara Rao, G. (Gorti) (Hoboken, N. J. : John Wiley & Sons, 2012)
'This book is a treatise on the basics of structural dynamics, typically taught across many engineering disciplines, often as an elective for the final year undergraduates or as a core course for 1st year MS/PhD students'--
Includes bibliographical references and index.
Keywords: Structural dynamics